INTERNALIZATION OF RELIGIOUS TOLERANCE ATTITUDES IN REALIZING P5PPRA AT ELEMENTARY SCHOOL LEVEL - Siregar, Nasyariah; Putri, Fia Alifah; Saputri, Vioni (LPPM Univ. Ibn Khaldun Bogor, 2024)
The purpose of devotion to public describe internalization attitude tolerance religious in implementing P5PPRA in the curriculum independent level school basic . With methodology study in the form of Participation Action Research (PAR) is A approach research involving​ participation active from the participants in all over stages research , start from formulation problems , planning , implementation , to taking decisions and actions continued . Research This conducted at SDN 28/IV Jambi City. The results of study This is that the community service program This No only give benefit direct to school basic , but also strengthens connection between college high and society . With share knowledge and experience , lecturer play a role as agent changes that occur to make smart life nation , started from generation young at the level basis . The result of activity This expected create impact term long in the form of improvement quality education and character more students​ good . And hope Finally is formation generation tolerant , inclusive and capable young people life peace in the middle diversity , in line with Pancasila values and Rahmatan Education little world.